PENGARUH FINANCIAL LITERACY, RISK PERCEPTION, BEHAVIORAL FINANCE DAN PENGALAMAN INVESTASI TERHADAP KEPUTUSAN INVESTASI MAHASISWA SURABAYA - WILDAN MUTAWALLY, FARIS; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2019)
The increasing of Single Investor Identification (SID) shows higher interest in investment activity. This investment activity requires a good investment decision with some factors that have influence to it. The purpose of this study is to determine the effect of financial literacy, risk perception, herding, illusion of control and investment experience factors toward investment decisions in investment gallery students in Surabaya. This study used multiple linear regression with 165 respondents where the respondents were students who became investors in 15 investment galleries in Surabaya. The results of the study show that herding variables and investment experience have an influence toward investment decisions. Respondents are in the group of investors who depend on their colleagues, friends or fellow investors as well as majority decisions without analyzing them first. Respondents are also included in the category of respondents who have sufficient experience in investment decisions so that the increasing experience will increase the number of investment decisions to hold various special alternatives for profitable alternative stocks.